Clinicopathological study of primary obstructive megaureter - Saravanan, C.; Vinayagam, Karpaga (International Surgery Journal, 2020)
Background: Megaureter is a non-specific term implying a spectrum of anomalies associated with pathologically excessive ureteral diameter. It implies no particular unifying pathophysiologic principles but merely groups together a spectrum of anomalies associated with increased ureteral diameter. To analyse the clinical profile and various investigation modalities used in diagnosing primary obstructive megaureter. Methods: This prospective study was conducted in March 2017 to August 2019 at the Institute of Child Health and Hospital for Children (ICH and HC), Egmore, Chennai. Results: The most common presentation was febrile urinary tract infection, second most presentation was asymptomatic patients, on post-natal evaluation of antenatally diagnosed cases. The most common finding on the antenatal scan is uretero-hydronephrosis. Maximum incidence of ureteric size - between 1 and 1.5 cms. 13 patients underwent surgery after an initial period of observation from the time of presentation. These patients belong to the period of infancy. The coincidence of circular muscle hyperplasia and longitudinal muscle hypoplasia was noted in 18 patients. Conclusions: In this study, patients presented during infancy were initially observed, prior to surgical intervention. But those patients presented beyond infancy were evaluated and intervened surgically during the same admission. Cohen’s uretero-neocystostomy through intra-vesical approach is the surgical procedure of choice, in the majority of the cases, in this study.